Design and Realization of a New Wheel-track Hybrid Electric Powered Wheelchair - Jia Yongxiang; Tao Weijun; Jing Tian; Feng Bin; Yin Yihong (Jixie chuandong)
Aiming at the requirement of the efficient move on the ground and safe stairs- climbing for some physical disabled or aged people,a new wheel- track hybrid electric powered wheelchair（ EPW） is designed. The technology solution of the wheel- track hybrid EPW is proposed and its mechanical structure and control system are designed. The process of climbing up and down the stairs in the track mobile mode is analyzed and diagrammatized. The prototype of this wheel- track hybrid EPW is manufactured and the experiments of climbing up and down the stairs are implemented. The experimental results show that the designed wheel-track hybrid EPW can realize the function of both moving on the ground efficiently and climbing up and down the stairs safely.